a) \(x\ne0;4\)
b) \(A=\left(1-\frac{4\sqrt{x}}{x-1}+\frac{1}{\sqrt{x}-1}\right):\frac{x-2\sqrt{x}}{x-1}\)
\(A=\left(\frac{x-1}{x-1}-\frac{4\sqrt{x}}{x-1}+\frac{\sqrt{x}+1}{x-1}\right)\cdot\frac{x-1}{x-2\sqrt{x}}\)
\(A=\frac{x-1-4\sqrt{x}+\sqrt{x}+1}{x-1}\cdot\frac{x-1}{\sqrt{x}\left(\sqrt{x}-2\right)}\)
\(A=\frac{x-3\sqrt{x}}{\sqrt{x}\left(\sqrt{x}-2\right)}\)
\(A=\frac{\sqrt{x}\left(\sqrt{x}-3\right)}{\sqrt{x}\left(\sqrt{x}-2\right)}\)
\(A=\frac{\sqrt{x}-3}{\sqrt{x}-2}\)
c) Phải là tìm giá trị nguyên của x chứ bạn ?
\(A=\frac{\sqrt{x}-3}{\sqrt{x}-2}=\frac{\sqrt{x}-2-1}{\sqrt{x}-2}=1-\frac{1}{\sqrt{x}-2}\)
Để A nguyên thì \(1⋮\sqrt{x}-2\)
\(\Leftrightarrow\sqrt{x}-2\inƯ\left(1\right)=1\)
\(\Leftrightarrow\sqrt{x}=3\)
\(\Leftrightarrow x=9\) ( thỏa )
Vậy....